Translation: A Continuous Process of Varied Readings - Abdulsalam Abdul Majeed Saiful ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Translation is a process that includes reading and interpretation. A text can be interpreted in various ways especially a literary one. Thus, there will be multiple translations / readings of different translators / readers of the same text, just as with the various translations / readings of As- Sayyab’s poem (Inshudat al-maTar) (Rain Song), Rilke’s poem The Panther, and Wild’s Short Story The Happy Prince. This study is based on Schulte Rainer’s assumption (1985) that translation is a constant process of readings and the text is thought to contain a possible range of interpretations. The findings showed that due to this variety of interpretations of the same texts, there will be multiple translations/ of different translators/readers of the same text. It is recommended that on the pedagogical levels students of translation should be trained on how to develop their interpretative capacities via enriching their comprehension abilities in intensive reading courses.